2018
DOI: 10.1002/fsn3.853
|View full text |Cite
|
Sign up to set email alerts
|

Dietary source of saturated fat and percentage body fat of patients with type 2 diabetes mellitus: A cross‐sectional study

Abstract: BackgroundThe influence of dietary fat on the body fat of patients with diabetes is not well established. This cross‐sectional study aimed to analyze the association between percentage body fat (PBF) and dietary sources of fat from the usual diet of patients with type 2 diabetes.MethodsOutpatients were submitted to PBF evaluation estimated by bioelectrical impedance. The patient's usual diet was assessed by a 3‐day weighed diet record (WDR), and compliance was analyzed by comparing the protein intake estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Diabetes is a common and complex disease with a long course, multiple complications and hard‐to‐heal characteristics (Duarte et al., 2019). Previous studies have indicated that insulin participates in the metabolism of glucose and lipids, and insulin resistance could reduce glucose consumption in the cells and induce abnormal lipid levels (Peppa et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is a common and complex disease with a long course, multiple complications and hard‐to‐heal characteristics (Duarte et al., 2019). Previous studies have indicated that insulin participates in the metabolism of glucose and lipids, and insulin resistance could reduce glucose consumption in the cells and induce abnormal lipid levels (Peppa et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Cheung et al [ 23 ] found that obese Chinese T2DM patients had significantly higher meat consumption compared to non-obese T2DM patients. In this line, Duarte et al [ 27 ] investigated the relationship between percentage body fat (PBF) and dietary sources of fat from the usual diet of Brazilian patients with T2DM. These authors found that the consumption of red meat was associated with higher PBF [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this line, Duarte et al [ 27 ] investigated the relationship between percentage body fat (PBF) and dietary sources of fat from the usual diet of Brazilian patients with T2DM. These authors found that the consumption of red meat was associated with higher PBF [ 27 ]. Furthermore, in the adjusted analysis, these same authors found that the higher tertile of processed meat intake was associated with increased PBF compared to the lower tertile [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in diabetic patients, the entire coagulation cascade is impaired. Disruption in the functions of insulin as a natural platelet antagonist and inflammatory responses due to fluctuations in blood sugar level in diabetic patients accelerate the platelet adhesion to the blood vessels (Barlovic et al, 2011;Duarte et al, 2019;Ko et al, 2018Ko et al, , 2019. Inflammatory responses characterized by elevated CRP cause vascular disease in patients (Zhang et al, 2014).…”
Section: Sesame and Diabetesmentioning
confidence: 99%